Patient Knowledge and Adherence to Sunscreen Application Guidelines in Dermatology Clinics at Makkah city - AlNodali, ‏Njoud Ibrahim Hussain; Almusalami, Mustafa Mohammedali; Jan, Hawazin Deldar; siddiqui, Asma yousif; ALQAHTANI, NOUF SAEED; Alharbi, ‏Emad Abdulaziz; Ahmed, Walaa Abdu; Aljuaid, Abdulaziz Awad; Alyamani, ‏Nawras Ali; Hasaballah, Abeer ashary (Journal of Posthumanism, 2024)
Sunscreens help prevent skin cancer, but they must be applied correctly to remain effective, a practice many patients do not fully comprehend and practice. This study aimed to assess the level of patient involvement and use of given treatment among patients seen in dermatology clinics in Makkah city. Researchers administered questionnaires to 140 patients in three settings to test their familiarity with application tips, frequency of correct application, and primary reasons for not applying them. Results reported that although more patients were familiar with easy application tips, including using an application with over 30 SPF, few were using them correctly and regularly. Primary reasons for nonadherence included misinterpreting application quantity and finding application inconvenient. These results reveal that more patient education in clinics is required to improve its application and reduce skin cancer susceptibility. Solutions proposed are easy-to-implement guide materials and clinic reminders to improve application correctness and minimize skin cancer risk.